2017
DOI: 10.3390/brainsci7010009
|View full text |Cite
|
Sign up to set email alerts
|

Single Electrode Deep Brain Stimulation with Dual Targeting at Dual Frequency for the Treatment of Chronic Pain: A Case Series and Review of the Literature

Abstract: Deep Brain Stimulation (DBS) has been used to target many deep brain structures for the treatment of chronic pain. The periaqueductal grey and periventricular grey (PAG/PVG) is an effective target but results are variable, sometimes short-lived or subject to tolerance. The centromedian intra-laminar parafascicular complex (CMPf) modulates medial pain pathways and CMPf DBS may address the affective aspects of pain perception. Stimulation of multiple deep brain targets may offer a strategy to optimize management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…In several studies, the CM nucleus has been suggested as a potentially effective DBS target for the treatment of Parkinson's disease (Caparros-Lefebvre et al, 1999;Mazzone et al, 2006;Peppe et al, 2008;Stefani et al, 2009) and Tourette syndrome (Houeto et al, 2005;Savica et al, 2012;Marano et al, 2019). The clinical surgeries targeting at CM also show treatment effect for the generalized epilepsy (Fisher et al, 1992;Velasco et al, 2007;Valentín et al, 2013;Li and Cook, 2018) and intractable neuropathic pain (Young et al, 1995;Hollingworth et al, 2017) by means of DBS or thalamotomy. The DBS surgery targeting the CM nucleus currently uses indirect ways in which a two-dimensional stereotactic atlas of the thalamus is superimposed on a CT or MRI scan relative to coarse anatomical landmarks including anterior and posterior commissures (Stefani et al, 2009;Son et al, 2016;.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, the CM nucleus has been suggested as a potentially effective DBS target for the treatment of Parkinson's disease (Caparros-Lefebvre et al, 1999;Mazzone et al, 2006;Peppe et al, 2008;Stefani et al, 2009) and Tourette syndrome (Houeto et al, 2005;Savica et al, 2012;Marano et al, 2019). The clinical surgeries targeting at CM also show treatment effect for the generalized epilepsy (Fisher et al, 1992;Velasco et al, 2007;Valentín et al, 2013;Li and Cook, 2018) and intractable neuropathic pain (Young et al, 1995;Hollingworth et al, 2017) by means of DBS or thalamotomy. The DBS surgery targeting the CM nucleus currently uses indirect ways in which a two-dimensional stereotactic atlas of the thalamus is superimposed on a CT or MRI scan relative to coarse anatomical landmarks including anterior and posterior commissures (Stefani et al, 2009;Son et al, 2016;.…”
Section: Discussionmentioning
confidence: 99%
“…Most were published as individual case reports, although several were part of larger single-group studies (including multiple case reports) that included only one patient with PLP. 81,83,85,96 Five of the cases 84,[89][90][91]97 were reported only as conference abstracts.…”
Section: Case Reportsmentioning
confidence: 99%
“…There were six case reports on SCS, 82,84,88,90-92 six on MCS 81,86,[93][94][95][96] and four on DBS. 83,85,87,97 There was also one case report of SCS and DRG stimulation being undertaken simultaneously 89 and one of MCS followed by DBS. 92 Follow-up time was at least a few months in most reports and several years in many.…”
Section: Case Reportsmentioning
confidence: 99%
“…Neuropathic pain in humans corresponds with increased activity of CMPf neurons (Hirato et al 1991). CMPf stimulation or ablation has been found to be helpful in the treatment of central pain and deafferentation pain (Hariz and Bergenheim 1995;Hollingworth et al 2017).…”
Section: The Peri-ventricular and Periaqueductal Graymentioning
confidence: 99%